A large polysaccharide produced by helicobacter hepaticus induces an anti-inflammatory gene signature in macrophages - Danne, C; Ryzhakov, G; Martínez-López, M; Ilott, N; Franchini, F; Cuskin, F; Lowe, E; Bullers, S; Arthur, J; Powrie, F (Cell Press, 2017)
Interactions between the host and its microbiota are of mutual benefit and promote health. Complex molecular pathways underlie this dialog, but the identity of microbe-derived molecules that mediate the mutualistic state remains elusive. Helicobacter hepaticus is a member of the mouse intestinal microbiota that is tolerated by the host. In the absence of an intact IL-10 signaling, H. hepaticus induces an IL-23-driven inflammatory response in the intestine. Here we investigate the interactions between H. hepaticus and host immune cells that may promote mutualism, and the microbe-derived molecule(s) involved. Our results show that H. hepaticus triggers early IL-10 induction in intestinal macrophages and produces a large soluble polysaccharide that activates a specific MSK/CREB-dependent anti-inflammatory and repair gene signature via the receptor TLR2. These data identify a host-bacterial interaction that promotes mutualistic mechanisms at the intestinal interface. Further understanding of this pathway may provide novel prevention and treatment strategies for inflammatory bowel disease.